Development of constructivist lessons in Environmental Science - Ejem, Lynnette A. (Bukidnon State University Library Research Journal, 2008)
The researcher developed constructivist-based lessons in Environmental Science (ES 101). To determine the topics for the lessons, an informal interview and consultations with colleagues were conducted. With the use of the Task Analysis Chart (TAC), the 5Es Constructivist Instructional Model and the researcher’s references, the lessons were developed. Six lessons were subjected to a validation process to improve and refine their content and so with the other features. The panel of experts evaluated the materials with respect to content accuracy, clarity and appropriateness. The lessons were also evaluated by the potential teacher-users. The results of the evaluation showed that the materials satisfy the provisions set in the criteria. It was found out that the lessons present contents which are accurate, clear and appropriate. The researcher considered the quantitative comments and suggestions of the experts in the revision of the lessons. The potential teacher-users’ feedbacks were also analyzed. The results revealed that the teachers found the lessons to be very interesting, relevant, meaningful, motivating, appealing and easy to follow and very efficient in facilitating teaching-learning activities, and with highly attainable and achievable objectives. These findings should encourage Environmental Science teachers to use developed materials which include activities that promote active learning and enhance the development of communication and science process skills. The constructivist lessons can serve as good supplementary materials in teaching Environmental Science. The developed lessons may also serve as a guide in developing constructivist lessons in other subjects.